An examination of labor productivity and labor efficiency on Kansas farms - Miller, Cole (Kansas State University, 2008)
The objective of this thesis is to examine differences in labor efficiency and to find what is driving those differences among Kansas farms. The results provide a quantified understanding of the variation in labor productivity and labor efficiency relating to three categories of variables: farm characteristics, financial performance, and specialization. This research uses regression estimates from a data set of 1,145 Kansas farms to quantify how farm characteristics are related to labor productivity and labor efficiency. There are two main models. Labor productivity, expressed as value of farm production divided by the number of workers, is regressed on three categories of variables: farm characteristics, financial performance, and specialization. Labor efficiency, expressed as labor costs divided by value of farm production, is also regressed on the same categories of variables. The research found that farm size, managerial ability, and age were the most influential and significant variables in the labor productivity model. Farm size, managerial ability, and land tenure were the most influential and significant variables in the labor efficiency model. Farm size is a variable important to both models, and when evaluated at $100,000 of VFP, labor productivity has a value of 152,122 and a labor efficiency value of 0.271 (all else constant). When evaluated at a VFP of $500,000, labor productivity and labor efficiency improve to values of 217,914 and 0.246, respectively.
Keywords: Labor Productivity; Labor Efficiency; Economics, Agricultural (0503)